ԼՂԻՄ-ում Ադրբեջանի իրականացրած քաղաքականությունը Հայ Առաքելական եկեղեցու նկատմամբ 1920-30-ական թթ. և հետևանքները - Բալայան, Մելանյա (Մատենադարան)
The policy of atheism, adopted by the Communist Party in the Soviet era, manifested itself in a rather different manner and scope in NKAO and other Armenian-populated areas intentionally annexed to Soviet Azerbaijan. Religious persecutions were perpetrated exclusively against the Christian clergy, churches and other Christian monuments were destroyed. This was carried out by the direct order of the Communist Party of Azerbaijan and under its supervision. In many places, Muslim monuments exist to this day while Christian ones have mostly disappeared. This clearly indicates that “atheism” was merely a pretext for realizing the policy of Turkey aimed at the final appropriation of captured Armenian territories. Политика атеизма, принятая Коммунистической партией в советский период, имела разные масштабы и проявления во включенной в состав советского Азербайджана НКАО и в других населенных армянами населеннных пунктах, целенаправленно аннексированных Азербайджаном. Религиозные преследования и разрушения зданий духовного значения применялись исключительно по отношению к христианскому духовенству и христианским памятникам. Все это исполнялось по приказу компартии Азербайджана и непосредственно под ее контролем. В упомянутых местах по сей день стоят мусульманские памятники, в то время как основная часть христианских была разрушена. Все это четко свидетельствует о том, что “атеизм” был всего лишь предлогом на пути турецкого плана по присвоению захваченных армянских земель.
Keywords: Հայ Առաքելական եկեղեցու պատմություն